SYMBOLIC CONSTRUCTS AND THEMATIC DEPTH IN ANTOINE DE SAINT-EXUPÉRY’S THE LITTLE PRINCE - Hasanah, Nurul; Manugeren, M (JOURNAL OF LANGUAGE, 2025)
This study explores the symbolic constructs and thematic intricacies in Antoine de Saint-Exupéry’s The Little Prince, with a particular focus on the novel’s most significant symbols and their interpretive depth. Recognizing that literary symbolism often transcends literal meaning, the research aims to analyze how specific symbols in the novel function not only as narrative devices but also as representations of broader philosophical and emotional themes. Employing a qualitative descriptive approach, the study contrasts the denotative meanings of selected symbols with their connotative and symbolic significance, using direct textual evidence from the novel. The analysis reveals that The Little Prince is rich in symbolic imagery—such as the fox, the rose, the baobab tree, the desert, and the stars—all of which serve as allegorical elements reflecting themes of love, loss, connection, responsibility, and existential insight. Ultimately, the study demonstrates that these symbolic elements contribute to the novel’s enduring emotional resonance and its philosophical depth, inviting readers to engage with its meaning on multiple interpretive levels.